(untitled) (Journal of Universal Science Research, 2023)
Piroplasmidiosis, commonly referred to as "tick fever," is a parasitic disease that affects a wide range of animals, including livestock and domestic pets.These parasites are transmitted through the bite of infected ticks and can cause serious health problems in affected animals. In this article, we will explore the spread of piroplasmidiosis and the crucial preventive measures that can help mitigate its impact on animal populations. The huge role of leading scientists in the study of protozooses.the development of methods of therapy and prevention, as well as immunobiological pathogen properties